Wnt-Frizzled Signaling Regulates Activity-Mediated Synapse Formation - Teo, Samuel; Salinas, Patricia C. (Frontiers in Molecular Neuroscience, 2021)
The formation of synapses is a tightly regulated process that requires the coordinated assembly of the presynaptic and postsynaptic sides. Defects in synaptogenesis during development or in the adult can lead to neurodevelopmental disorders, neurological disorders and neurodegenerative diseases. In order to develop therapeutic approaches for these neurological conditions, we must first understand the molecular mechanisms that regulate synapse formation. The Wnt family of secreted glycoproteins are key regulators of synapse formation in different model systems from invertebrates to mammals. In this review, we will discuss the role of Wnt signaling in the formation of excitatory synapses in the mammalian brain by focusing on Wnt7a and Wnt5a, two Wnt ligands that play an in vivo role in this process. We will also discuss how changes in neuronal activity modulate the expression and/or release of Wnts, resulting in changes in the localization of surface levels of Frizzled, key Wnt receptors, at the synapse. Thus, changes in neuronal activity influence the magnitude of Wnt signaling, which in turn contributes to activity-mediated synapse formation.